The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1021/acs.est.0c08604
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Sources Govern Organic Aerosol Fractions with Different Degrees of Oxygenation in the Urban Atmosphere

Abstract: Understanding how the sources of an atmospheric organic aerosol (OA) govern its burden is crucial for assessing its impact on the environment and adopting proper control strategies. In this study, the sources of OA over Beijing were assessed yeararound based on the combination of two separation approaches for OA, one from chemical fractionation into the high-polarity fraction of water-soluble organic matter (HP-WSOM), humic-like substances (HULIS), and water-insoluble organic matter (WISOM), and the other from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 58 publications
0
23
0
2
Order By: Relevance
“…The dried samples were reconstituted with either 2 mL of ultrapure water or methanol for subsequent analyses. A recent study demonstrated that sequential solvent extraction of filter samples using an ultrasonic bath can quantitatively extract OM …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dried samples were reconstituted with either 2 mL of ultrapure water or methanol for subsequent analyses. A recent study demonstrated that sequential solvent extraction of filter samples using an ultrasonic bath can quantitatively extract OM …”
Section: Materials and Methodsmentioning
confidence: 99%
“…A recent study demonstrated that sequential solvent extraction of filter samples using an ultrasonic bath can quantitatively extract OM. 88 3.3. Separation of WSOM by the 1-Octanol−Water Extraction Method.…”
Section: Extractions Of Wsom and Wims-ommentioning
confidence: 99%
“…Solvent extraction from filter samples has been widely used to extract OA with different polarities. Water and alcohol solvents have been widely used to differentiate BrC components according to polarity and to evaluate the absorbing properties for each component. However, water-soluble OA only represents a limited fraction of the total OA, which accounts for 20–70% of OA and even as low as 20% in some urban environment, , depending on the aging time of aerosols. The extraction efficiency of methanol can reach 80–90%. , Other heavier solvents, such as dichloromethane and hexane, were also used to extract even lower polar OA. , OA at higher molecular weights can be extracted by lower polar solvents, which were found to have higher absorptivity than the more polar water-extractable OA (WSOA). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to HULIS, OA are also composed of highly polar water-soluble organic matter (HP-WSOM) and water-insoluble organic matter (WISOM). Zhou et al 17 found that the HP-WSOM fraction was most abundant in Beijing, whereas Chen et al 11 found that WISOM was most abundant in Nagoya. Both of these studies reported that HP-WSOM has high O/C ratios (mean: 1.37 and 0.99), while WISOM has low O/C ratios (mean: 0.17 and 0.14) 11 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al 17 found that the HP-WSOM fraction was most abundant in Beijing, whereas Chen et al 11 found that WISOM was most abundant in Nagoya. Both of these studies reported that HP-WSOM has high O/C ratios (mean: 1.37 and 0.99), while WISOM has low O/C ratios (mean: 0.17 and 0.14) 11 , 17 . Only a few studies have been reported about the abundance and chemical characteristics of these fractions, although the information is essential to characterize total OA in terms of the fractional contributions of HULIS and non-HULIS fractions.…”
Section: Introductionmentioning
confidence: 99%